Influence of prion variant and yeast strain variation on prion-molecular chaperone requirements - Hines, Justin K (Landes Bioscience, 2011)
Prions of budding yeast serve as a tractable model of amyloid behavior. Here we address the issue of the effect of yeast strain variation on prion stability, focusing also on the effect of amyloid conformation and the involvement of the co-chaperone Sis1, an essential J-protein partner of Hsp70. We found, despite an initial report to the contrary, that yeast strain background has little effect on the requirement for particular Sis1 domains for stable propagation of the prion [RNQ(+)], if the level of Sis1 expression is controlled. On the other hand, some variation in prion behavior was observed between yeast strains, in particular, the stability of certain [PSI(+)] variants. Future examination of such yeast strain-specific phenomena may provide useful insights into the basis of prion/chaperone dynamics.